Amphiphilic Triazine Polymer Derivatives as Antibacterial And Anti-atopic Agents in Mice Model - Gunasekaran, Pethaiah (Sci Rep, 2019)
Considering the emergence of bacterial resistance and low proteolytic stability of antimicrobial peptides (AMPs), herein we developed a series of ultra-short triazine based amphipathic polymers (TZP) that are connected with ethylene diamine linkers instead of protease sensitive amide bond. The most potent oligomers, TZP3 and TZP5 not only displayed potent antibacterial action on various drug-resistant pathogens but also exhibited a strong synergic antibacterial activity in combination with chloramphenicol against multidrug-resistant Pseudomonas aeruginosa (MDRPA). Since most of atopic dermatitis (AD) infections are caused by bacterial colonization, we evaluated the potency of TZP3 and TZP5 on AD in vitro and in vivo. In vitro AD analysis of these two polymers showed significant inhibition against the release of β-hexosaminidase and tumor necrosis factor (TNF-α) from RBL-2H3 cells. In AD-like skin lesions in BALB/c mice model, these two polymers displayed significant potency in suppressing dermal and epidermal thickness, mast cell infiltration and pro-inflammatory cytokines expression. Moreover, these polymers exhibited remarkable efficacy over the allergies caused by the imbalance of Th1/Th2 by regulating total IgE and IgG2a. Finally, the impact of treatment effects of these polymers was examined through analyzing the weights and sizes of spleen and lymph node of AD-induced mice.